Impact of dietary bee honey during first weeks of life in dairy lambs on growth and metabolism - de Oliveira Cecere B.G.* (2020)
© 2019, Springer-Verlag London Ltd., part of Springer Nature.Bee honey has beneficial properties that are recognized worldwide, including high nutritional value. The objective of this study was to determine whether a daily dose of honey would improve productive performance as well as energy, protein, and lipid metabolisms in lactating lambs. Bee honey (from Apis mellifera) was offered orally for the first 7 days of the animals’ lives. Twenty Lacaune lambs were used, allocated to two groups: group C, lambs not supplemented with honey, and group T, consisting of lambs fed daily doses of 10 mL of honey. The experimental period lasted 45 days. Body weight measurements and blood sample collections were performed at five time points (days 1, 7, 15, 30, and 45 of life). The lambs that consumed honey showed significantly greater weight gain during the experimental period; there was greater weight gain between days of life 30 and 45. We found significantly higher levels of urea (days 30 and 45) and globulins (day 45). Carbohydrate (glucose), lipid (triglycerides and cholesterol), and protein (total protein and albumin) levels did not differ between treatments. Based on these preliminary results, we conclude that supplementation with honey in the lamb diets may stimulate growth in during lactating phase.